Isolation of compound from root of morinda citrifolia / Muhammad Amirul Afify Mohd. Ghani - Mohd. Ghani, Muhammad Amirul Afify (Faculty Of Applied Sciences, 2019)
Extensive work on the isolating metabolites from Malaysia flora, roots of Morinda citrifolia was chosen for further phytochemical analysis. This plant was going for detail separation work which involves extraction and isolation of chemical component using a various technique of analysis. Rubiaidin was found as component from isolation of this plant. Detail work on the solvent extract of Morinda citrifolia has afforded rubiadin and nordamnacanthal. These pure compounds were elucidated by using numerous spectroscopic analysis like 1H and l3C NMR, IR, UV and by comparison with the previous works.